Towards better monitoring of innovation strengths, regional specialisation and industrial modernisation in the EU. Report - Els Van de Velde; Jean-François Romainville; Henning Kroll; Sven Wydra; Christian Rammer; Kincsö Izsak; Paresa Markianidou; Carolina Spaini; Antonio Collado; Inga Sabanova (Publications Office of the European Union, 2019)
This study on the monitoring of innovation strengths, regional specialisation and industrial modernisation in the European Union has two main aims. The first is to verify whether the existing indicators and data sources provide a sufficient basis for monitoring relevant aspects of industrial modernisation in the European Union, while the second is to propose a grounded system of indicators to measure industrial modernisation. The future monitoring of industrial modernisation will need to cover different aspects. The monitoring system proposed in this report focuses on industrial modernisation as a transformative process that aims at improving the competitiveness of European manufacturing in an increasingly competitive global environment. Industrial modernisation has to address the upcoming challenges facing manufacturing in Europe as well as to respond to new opportunities of production, including the changes resulting from digitalisation and other new technologies.
Additional information: Project number: EASME/COSME/2016/014
Keywords: 330